"I Wanna Be Sedated": A Closer Examination of Psychosocial Factors Associated With Past-Year Tranquilizer Use Among National Sample of Sexual Minority Adults. (January 2020) - Yockey, R. Andrew; King, Keith A.; Vidourek, Rebecca A.
Sexual minorities are at increased risk of substance use disorders. Gaps in the research exist regarding tranquilizer use among sexual minorities. Identifying risk factors associated with tranquilizer use may assist public health professionals in developing specific interventions for this vulnerable population. The present study examined potential factors associated with past-year tranquilizer use among a national sample of sexual minorities. A secondary data analysis of the 2017 National Survey on Drug Use and Health was conducted. Results revealed that one in five (21.9%) sexual minorities used a tranquilizer within the past year. Associated risk factors included being female, 18 years of age or older, past-year use of illicit drugs, and having lost interest or pleasure in once pleasurable activities. Findings from the present study can assist prevention professionals in further developing and implementing initiatives to mitigate tranquilizer use among sexual minorities.